2023
DOI: 10.1002/asia.202300328
|View full text |Cite
|
Sign up to set email alerts
|

A BODIPY‐Based 1D Covalent Organic Framework for Photocatalytic Aerobic Oxidation

Abstract: Covalent organic frameworks (COFs) as metal‐free photocatalysts have attracted extensive interest. However, the organic transformations photocatalyzed by COFs under mild conditions remain a challenge. Herein, a boron‐dipyrromethene (BODIPY) based 1D COF, namely JNM‐12, was facilely constructed by Schiff‐base condensation reaction. JNM‐12 exhibited strong visible‐light harvesting abilities and suitable photocatalysis energy potentials, enabling the activation of O2 to superoxide anions (O2⋅−) and singlet oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…[85] This instability poses challenges in integrating them into COF structures. [86,87] Similarly, the susceptibility of thiol (À SH) groups to oxidation, [88][89][90] particularly at elevated temperatures, presents a hurdle. This often results in the need for intricate postmodification processes when incorporating the SH group into COF side chains.…”
Section: Discussionmentioning
confidence: 99%
“…[85] This instability poses challenges in integrating them into COF structures. [86,87] Similarly, the susceptibility of thiol (À SH) groups to oxidation, [88][89][90] particularly at elevated temperatures, presents a hurdle. This often results in the need for intricate postmodification processes when incorporating the SH group into COF side chains.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu and co-workers fabricated supramolecular assembly through host–guest interactions between water-soluble pillar[5]­arene and an aggregation-induced emission (AIE) photosensitizer, which exhibit the ability to effectively generate 1 O 2 and can be used as PCs for the conversion of dopamine to polydopamine . Li and co-workers reported a BODIPY-based one-dimensional covalent organic framework which not only has the ability to produce photoactive substances but also can be used to photocatalyze the oxidative coupling reaction of benzylamine . Chen and co-workers developed a BODPIY-based metal–organic framework that transforms from one-dimensional chains to two-dimensional layer structures, which can be used as an efficient visible light heterogeneous PC for the construction of C–B and C–C bonds .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, SCN is the first sp 2 -carbon conjugated 2D COF with staggered stacking . The staggered stacking introduced disorder and reduced the crystallinity of SCN …”
mentioning
confidence: 99%
“…40 The staggered stacking introduced disorder and reduced the crystallinity of SCN. 35 X-ray photoelectron spectroscopy (XPS) showed that NiSCN had Ni(II) centers with Ni 2p 1/2 and 2p 3/2 peaks at 872.85 and 875.44 eV, respectively (Figure S3). Extended Xray absorption fine structure (EXAFS) analysis showed that the Ni centers in NiSCN adopted a tetrahedral coordination environment similar to that of Ni(bpy)Br 2 with two Ni−N bonds at 1.98 Å and two Ni−Br bonds at 2.35 Å (Figure 2d).…”
mentioning
confidence: 99%
See 1 more Smart Citation